Effects of blood flow restriction without additional exercise on strength reductions and muscular atrophy following immobilization: A systematic review - Mikhail Santos Cerqueira; José Diego Sales Do Nascimento; Daniel Germano Maciel; Jean Artur Mendonça Barboza; Wouber Hérickson De Brito Vieira (Elsevier, 2020)
Purpose: To investigate whether blood flow restriction (BFR) without concomitant exercise mitigated strength reduction and atrophy of thigh muscles in subjects under immobilization for lower limbs. Methods: The following databases were searched: PubMed, CINAHL, PEDro, Web of Science, Central, and Scopus. Results: The search identified 3 eligible studies, and the total sample in the identified studies consisted of 38 participants. Isokinetic and isometric torque of the knee flexors and extensors was examined in 2 studies. Cross-sectional area of thigh muscles was evaluated in 1 study, and thigh girth was measured in 2 studies. The BFR protocol was 5 sets of 5 min of occlusion and 3 min of free flow, twice daily for approximately 2 weeks. As a whole, the included studies indicate that BFR without exercise is able to minimize strength reduction and muscular atrophy after immobilization. It is crucial to emphasize, however, that the included studies showed a high risk of bias, especially regarding allocation concealment, blinding of outcome assessment, intention-to-treat analyses, and group similarity at baseline. Conclusion: Although potentially useful, the high risk of bias presented by original studies limits the indication of BFR without concomitant exercise as an effective countermeasure against strength reduction and atrophy mediated by immobilization. Keywords: Disuse, Hypoxia, Ischemia, Muscle wasting, Rehabilitation